The Effectiveness of Transcranial Direct Current Stimulation and Multi- Component Cognitive Stimulation Programs on Cognitive Functions and Quality of Life in Elderly - Bakhtiar Moslemi; Gholamreza Chalabianloo (مطالعات روانشناختی)
The purpose of this study was to examine the effect of transcranial direct current stimulation and multi-component cognitive stimulation of the prefrontal cortex on cognitive function and quality of life in the elderly. The present study was a quasi-experimental investigation using a pretest-posttest and follow up and a control group design. The statistical population of the research was all elderly people living in Tabriz city from 2023. A sample of 90 elderly people over 60 years of age, were randomly assigned to in three groups of transcranial direct current stimulation and multi-component cognitive stimulation and control groups. Experimental group received Transcranial Direct Current Stimulation (tDCS) on the prefrontal cortex, for the second group, multi-component cognitive stimulation software was used for three months and control group did not receive any intervention. The CANTAB test was used to evaluate cognitive function as well as  QOL-SF 36 questionnaire. The data  analysis were used by analysis varainces with repeated measure. The results indicated that tDCS and multi-component cognitive stimulation were effective on the cognitive function and quality of life of the elderly.